The Impact of Customer Satisfaction on Loyalty in the Ghana Banking Sector: The Effect of Trust Mediation - Banahene, Stephen (Advances in Social Sciences Research Journal, 2018)
Customer satisfaction, trust and loyalty have been extensively researched, but the continuous changing of customer needs and the changing banking regulatory environment necessitates a correspondingly continuous evaluation of these construct. This study analysed the impact that customer satisfaction has on customer loyalty. In addition, the study investigated the mediating role of trust in the relationship between customer satisfaction and customer loyalty. The study was conducted on 825 useable responses which represented 82.5% of questionnaires distributed. Explanatory research design was used and Stata version 13 and IBM Statistical Package for Social Sciences version 20 were the software used in data analysis. The study used Structural Equation Model for data analysis to explored direct, indirect and total effect relationships. Confirmatory Factor Analysis was used for data purification. The study concludes that customer satisfaction has positive and significant relationship with customer loyalty in the banking sector. The study also found that customer satisfaction positively and significantly affects customer trust in the banking sector. In addition, customer trust also affects customer loyalty positively and significantly. The study also revealed that customer trust partially mediates between customer satisfaction and customer loyalty. However, customer trust does not mediate between specific dimensions of customer satisfaction and customer loyalty. This means that researchers and managers of banks should find innovative ways to build service performance and aligned their services to as a way to increase customer satisfaction to promote customer loyalty. The customer trust partial mediation role and customer trust failure to mediate customer satisfaction specific dimensions with customer loyalty need future research.